2 New COVID initiative – introduction of the just in time emergency medicine pack (JEMP). Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Jones, E; Jayham, A; Francis, M; Casey, W; Griffiths, G; Gibbins, A; Crabtree, A; Hayes, J
Abstract : Background: During the coronavirus pandemic, it was essential to ensure access to End of life (EoL) medications while protecting the medications supply chain. Traditional Just in Case prescribing could have exhausted the national supply. Consequently, a new NHS Wales Interim End of Life COVID-19 Medicines Service was implemented to provide access to a medication box a Just-In-Time Emergency Medication Pack (JEMP). Methods: The JEMP scheme ensured that end of life medications could be delivered directly to the patient within 2 hours, 24 hours a day 7 days a week, across the whole of Wales. The JEMP contained an agreed list of medications. The Health Courier Service Wales managed a Single Point of Contact, and directed the JEMP request to the most appropriate EoL Pharmacy Hub situated at one of five strategic sites around Wales. To access the service, a healthcare professional would call a 24/7 phone line and send a digital image of the prescription for EoL medications via Hospify (like an NHS Whatsapp). The JEMP then would be delivered directly to the patient's house and the prescription would be collected. Results: 17 requests were activated. 1 call was stood down. 15 out of the 16 requests had a JEMP delivered within 2 hours. This ranged from 34 minutes to 111 minutes. The mean time was 72 minutes. Conclusion: This is a pioneering service that developed during the coronavirus pandemic, it went from concept to a national pilot in 6 days. The uptake of services was less than originally predicted. However, it has been successful in its primary aims to maintain the supply chain and deliver vital EoL medications directly to the patient anywhere in Wales (24 hours 7 days a week) within 2 hours from the initial request. Further work needs to be done on collecting feedback and assessing sustainability.